Label-Free Quantitative Proteomic Analysis Provides Insight Into the Differences Between Slow-Twitch Muscle and Fast-Twitch Muscle of Pseudocaranx dentex - Wang, Huan; Li, Busu; Li, Jiefeng; Jiang, Chen; Liu, Shufang; Zhuang, Zhimeng (Frontiers in Marine Science, 2022)
Fish skeletal muscles are mainly composed of two distinct types, fast-twitch and slow-twitch muscles, and they play important roles in maintaining movement and energy metabolism. The fast-twitch muscle contracts quickly and is mainly responsible for burst swimming, while the slow-twitch muscle possesses fatigue resistance and supports endurance swimming. To assess the differences in molecular composition and investigate the potential regulatory mechanisms, we performed an integrative study at both proteomic and transcriptomic levels of the fast-twitch and slow-twitch muscles in Pseudocaranx dentex, a pelagic migratory fish with distinctly differentiated skeletal muscle. Label-free proteomics revealed 471 differentially expressed proteins (DEPs), 422 upregulated and 49 downregulated in slow-twitch muscle when compared to fast-twitch muscle. These DEPs were mainly involved in myofibrillary structure and energy metabolism. Integrative analysis of proteomic and transcriptomic data showed that 757 RNA-protein pairs were positively correlated, and 191 RNA-protein pairs were negatively correlated in abundance. Meanwhile, 311 RNA-protein pairs were consistent in fold changes, and 594 RNA-protein pairs exhibited striking differences, which provided an insight into the complex regulation at both transcriptional and post-transcriptional levels that contribute to shaping the different muscle types. The specific expression of multiple myofibrillar proteins, such as myosin, actin, troponin, and tropomyosin, suggested that the distinction in contraction characterizations between slow-twitch and fast-twitch muscles is related to different protein isoforms. Muscle-type specific expression of gene-encoding key enzymes in fatty acid metabolism, glycolysis, tricarboxylic acid (TCA) cycle, and oxidative phosphorylation pathways, such as carnitine palmitoyltransferase (CPT2), phosphofructokinase (Pfkm), pyruvate kinase (Pkmb), citrate synthase (CS), isocitrate dehydrogenase (IDH), and 2-oxoglutarate dehydrogenase complex (Ogdh), may be the molecular basis responsible for the differences in energy metabolism. Overall, this global view of protein and RNA expression levels in P. dentex fast-twitch and slow-twitch muscles reveals the essential roles of transcriptional and post-transcriptional regulation in maintaining muscle structure and function. The identified potential genes that may cause the differences in physiological characteristics will greatly improve our understanding on the molecular basis of skeletal muscle contraction, metabolism, and regulation in teleost.